Validation of the Spanish Version of the Psychological Sense of School Membership (PSSM) Scale in Chilean Adolescents and Its Association with School-Related Outcomes and Substance Use - Gaete, Jorge; Montero-Marin, Jesus; Rojas-Barahona, Cristian A.; Olivares, Esterbina; Araya, Ricardo (Frontiers in Psychology, 2016)
School membership appears to be an important factor in explaining the relationship between students and schools, including school staff. School membership is associated with several school-related outcomes, such as academic performance and expectations. Most studies on school membership have been conducted in developed countries. The Psychological Sense of School Membership (PSSM) scale (18 items: 13 positively worded items, 5 negatively worded items) has been widely used to measure this construct, but no studies regarding its validity and reliability have been conducted in Spanish-speaking Latin American countries. This study investigates the psychometric properties, factor structure and reliability of this scale in a sample of 1250 early adolescents in Chile. Both exploratory and confirmatory factor analyses provide evidence of an excellent fit for a one-factor solution after removing the negatively worded items. The internal consistency of this new abbreviated version was 0.92. The association analyses demonstrated that high school membership was associated with better academic performance, stronger school bonding, a reduced likelihood of school misbehavior and reduced likelihood of substance use. Analyses showed support for the reliability and validity of the PSSM among Chilean adolescents.